NEOLIBERALISM OF THE SOUTH: AN APPROACH TO THE BRAZILIAN PRISON SYSTEM - Bora, Siddharth Singh; Bora, Zelia Monteiro (Revista Debates Insubmissos, 2020)
Neoliberalism indirectly sustains the prison rates in peripheral South economies like Brazil. The precariousness bred by a welfare-averse politics maintains a steady flow of inmates. The Brazilian Penal state focuses on devising micro interventions to fight the crime rates. As a direct consequence, the state is bounded to segregate and imprison more. Brazil has the third largest prison population in the world The crisis of the Brazilian penitentiary system is not a contingency of today but of parameters of social-historical continuity, the result of a long historical process originated from the birth of the institution in colonial times. Palavras-chaves: prisão, encarceramento em massa, neoliberalismo.